IMPACT OF AFLATOXIN B1 ON GROWTH PERFORMANCE AND HISTOPATHOLOGICAL CHANGES IN CYPRINUS CARPIO - Aseel G. Rhadi; A. J. Al-Rudainy; R. S. Attee (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study aimed to identify the impact of aflatoxin B1 (AFB1)-contaminated diet on growth performance and histopathological changes of the kidney and muscle tissues in Cyprinus carpio . A total of 300 fish with an average of weight 45±5 g, were randomly distributed into 15 plastic tanks, and were divided into five experimental groups; (group 1) served as control , fish fed  normal diet without solvent and AFB1, (group 2) positive control fish were fed with only solvent, and (groups 3-5) fish were fed diets containing 0.5, 1 and 2 mg AFB1/kg of feed, respectively. Results showed the negative effect for AFB1 on weight gain, average daily gain of fish. Histopathological changes of kidney and muscles in AFB1-treated fish showed devastation of the renal tract, glomerular atrophy with necrosis, expansion of Bowman’s space, necrosis in urinary tubules, peeling and degradation in the epithelium of tubules, vascular congestion, and interstitial hemorrhage associated with mononuclear cells (MNCs) infiltration with tubules, increased of urinary lumen space, and increase of melano-macrophage   centers (MMC). The results also showed a significant damage to the structure of muscles as a result of the disintegration of muscle fibers, which increased with the increase in the AB1 concentrations.